2018
DOI: 10.5539/ies.v11n5p144
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Facebook Activities on Enhancing Oral Communication Skills for EFL Learners

Abstract: This study investigated the effect of utilizing Facebook activities on enhancing oral communication skills for English as Foreign Language learners (EFL) in the English Department at Yarmouk University, Jordan. Participants of the study were first year English Language Bachelor degree students who speak English as a foreign language. The researcher hypothesized that if these learners practiced Facebook activities, their oral communication skills may be improved. For answering questions of the study, the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
2
7
0
1
Order By: Relevance
“…Based on these findings, it can be seen that past research in the Arab EFL context conform to the results of high usage of digital technologies for teaching and learning listening [40], and [41] found that digital technology has improved students' listening skills. Regarding speaking skills, the findings of the study are in line with the findings reached by [42][43][44], who found that digital technologies have a positive impact on students' speaking skills. Al-Ahdal [44] used a computer software system to analyze students errors to improve students' speaking, Al-Saleem [42] found that Facebook activities enhanced students' oral communication, while Minalla [43] concluded that WhatsApp application chat groups developed students' verbal interactions, Hamad et al [45] used the YouTube application to improve students speaking skills and concluded that YouTube has a positive impact on EFL students' speaking skills.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Based on these findings, it can be seen that past research in the Arab EFL context conform to the results of high usage of digital technologies for teaching and learning listening [40], and [41] found that digital technology has improved students' listening skills. Regarding speaking skills, the findings of the study are in line with the findings reached by [42][43][44], who found that digital technologies have a positive impact on students' speaking skills. Al-Ahdal [44] used a computer software system to analyze students errors to improve students' speaking, Al-Saleem [42] found that Facebook activities enhanced students' oral communication, while Minalla [43] concluded that WhatsApp application chat groups developed students' verbal interactions, Hamad et al [45] used the YouTube application to improve students speaking skills and concluded that YouTube has a positive impact on EFL students' speaking skills.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding speaking skills, the findings of the study are in line with the findings reached by [42][43][44], who found that digital technologies have a positive impact on students' speaking skills. Al-Ahdal [44] used a computer software system to analyze students errors to improve students' speaking, Al-Saleem [42] found that Facebook activities enhanced students' oral communication, while Minalla [43] concluded that WhatsApp application chat groups developed students' verbal interactions, Hamad et al [45] used the YouTube application to improve students speaking skills and concluded that YouTube has a positive impact on EFL students' speaking skills. Additionally, the findings of the writing skill are in line with the outcomes of the following past studies that have used the following digital technologies: weblog [41], screen-casting [46], wikis [47], flipped classroom [48], Facebook [49], portfolio [50], and WhatsApp [51].…”
Section: Discussionsupporting
confidence: 88%
“…In terms of the effects of e-learning in teaching and learning of speaking skill, all of the past studies (n= 10) revealed positive results despite some limitations encountered in elearning. Studies showed that the use of ICT tools and digital platforms in e-learning were able to motive the learners, enhance four language skills particularly oral communication skills and encourage autonomous learning (Mošatová & Výškrabková, 2019;Banditvilai, 2016;AlSaleem, 2018). There were also studies which revealed that the use of e-learning could improve speaking skills in terms of grammar rules, word usage, intonation and pronunciation while some studies suggested that it helped to develop fluency, coherence, lexical resources and accuracy skills (Tseng & Yeh, 2019;Köroğlu & Çakır, 2017;Herrera Díaz & González Miy, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Anyhow, technologies, and social media sites would alter human interaction and relationships, society, and environment. Because of this, a great deal of work was carried out to study the influence of social media on interpersonal communication on various types of relationships, such as adolescent friendship (Gapsiso & Wilson, 2015;Lenhart et al, 2007;Ndunge, 2017;Subrahmanyam & Greenfield, 2008), teacher-student relationships (Alsaleem, 2018;Keasberry, 2018;Mazer et al, 2007) and family members (Mesch, 2006;Mauthner & Kazimierczak, 2019;Ngonidzashe, 2016;Pace et al, 2013). In addition, social media can also significantly impact intimate relationships.…”
Section: Introductionmentioning
confidence: 99%